Gunung Tahan Trail: a historical review - Yaakob, Sam Shor Nahar; Amri, Saidon; Aziz, Azlizam; Y. H., Mohd; Abdullah, Z. (Forestry Department Peninsular Malaysia, 2009)
There are still a lot of information on the history of Gunung Tahan Trail which remain unknown to the Malaysian public; some were buried with the demise of the elderly living around this mountain. This paper attempts to reveal the history of this famous trail which is located in Taman Negara in relation to the origin of its name, local belief and folklore of the mountain, colonial proposal for the establishment of grand hill station and early attempts to explore the mountain. Most of the data and information for this review were gathered from field notes and expedition reports published in various journals between 1880 and 1940. These information would be useful to Taman Negara Park Management in enriching recreational and nature tourism experiences among users of Gunung Tahan Trail.